Download presentation
Presentation is loading. Please wait.
Published byMaría Luz Álvarez Modified over 5 years ago
1
5.6 - Solving Logarithmic and Exponential Equations
Exponentials: ln(ex) = x… so if ex = 2… ln(ex) = ln(2) x = ln(2) ex: ex + 5 = 60 ex = 55 ln(ex) = ln(55) x = ln(55) ex: 4e2x = 5 e2x = 5/4 ln(e2x) = ln(5/4) 2x = ln(5/4) x = ln(5/4) / 2
2
ex: e2x - 3ex + 2 = 0 (ex - 2) (ex - 1) = 0 ex: Other Bases 2x = 10 ln(2x) = ln(10) x ln(2) = ln(10) x = ln(10) / ln(2) = 3.322 (ex - 2) = 0 ex = 2 ln(ex) = ln(2) x = ln(2) = 0.693 (ex - 1) = 0 ex = 1 ln(ex) = ln(1) x = 0
3
Finding Solutions Graphically
2) Set equation = 0 Graph Find zero(s) ex: 2x = 10 3) 1)
4
IC 5.6A - pg 386 #’s 1, 2, 4, 5, 8, 10, 11, 14, 15, 18, 19, 22, 25, 26, 30, 31, 34.
5
e(ln 3x) = e2 Solving Logarithmic Equations
Exponentials and logs are inverse functions So for logs we raise both sides of the equation up as exponents…the base of the exponential we are creating is the base of the log statement (e for ln’s / whatever ‘a’ is for logs) We call this ‘exponentiation’ ex: ln x = 3 eln x = e3 x = e3 5 + 2ln x = 4 2ln x = -1 ln x = -1/2 eln x = e(-1/2) x = e(-1/2) 2ln 3x = 4 ln 3x = 2 e(ln 3x) = e2 3x = e2 x = e2/3
6
2(log23x) = 22 = 64 Other Bases ex: log4x = 3 4(log4x) = 43 x = 43
7
Shortcut ex: log10(x + 2) = log10 (3x - 4) Drop log statements (x + 2) = (3x - 4) 2x = 6 x = 3 Multiple log (or ln) statements ln(x - 3) + ln(2x + 1) = 2(ln x) Combine with laws of logs ln[(x – 3)(2x + 1)] = ln x2 Drop log statements (x – 3)(2x + 1) = x2 2x2 - 5x – 3 = x2 x2 - 5x – 3 = 0 Factor / Graph
8
Creating log (or ln) statements from constants
loga ax = x so… log10 10 = 1 ln e = 1 ln e2 = 2 ln e3 = 3 log = 2 log = 3 etc… ex: 2 + ln (x + 4) = ln 16 ln e2 + ln (x + 4) = ln 16 ln e2 (x + 4) = ln 16 Combine log statements e2 (x + 4) = 16 Drop log statements x = (16/e2) - 4
9
IC 5.6B – pg 386 #’s 37, 38, 41, 42, all, 52.
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.